2018
DOI: 10.1364/oe.26.002829
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a broad-band quantum cascade laser: from chaos to coherent dynamics and mode-locking

Abstract: Abstract:The dynamics of a multimode Quantum Cascade Laser, is studied in a model based on effective semiconductor Maxwell-Bloch equations, encompassing key features for the radiationmedium interaction such as an asymmetric, frequency dependent, gain and refractive index as well as the phase-amplitude coupling provided by the Henry factor. By considering the role of the free spectral range and Henry factor, we develop criteria suitable to identify the conditions which allow to destabilize, close to threshold, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…For QCLs, the MB equations have primarily been used to study ultrashort pulse generation by mode‐locking and the closely related formation of coherent instabilities, as well as the generation of frequency combs . In detail, it has been found that coherent multimode instabilities result in the emergence of sidebands around the original longitudinal mode, giving rise to broadband multimode operation .…”
Section: Application To Optoelectronic Devicesmentioning
confidence: 99%
“…For QCLs, the MB equations have primarily been used to study ultrashort pulse generation by mode‐locking and the closely related formation of coherent instabilities, as well as the generation of frequency combs . In detail, it has been found that coherent multimode instabilities result in the emergence of sidebands around the original longitudinal mode, giving rise to broadband multimode operation .…”
Section: Application To Optoelectronic Devicesmentioning
confidence: 99%
“…The realization, nearly 13 years ago, of frequency combs in high-Q monolithic microresonators filled with Kerr media [3] raised an enormous attention because of its potential for miniaturization and chip-scale photonic integration, and stimulated a great deal of activities [4][5][6]. More recently, another system relevant for photonic integration, namely the quantum cascade laser (QCL) emerged as a source of frequency combs [7][8][9][10][11][12]. Close to its lasing threshold, the dynamics of a QCL is governed by a cubic nonlinearity similar to the one of Kerr cavities.…”
Section: Introductionmentioning
confidence: 99%
“…A relevant point is that while in the passive case frequency combs need an external field providing the necessary energy intake, in active systems like the QCL frequency combs are generated in a free-running setup [7,[9][10][11][12][13]. The generalized LLE also contemplates a novel configuration, to our knowledge never analysed before, in which a ring QCL is driven by an external coherent field (QCL with injected signal).…”
Section: Introductionmentioning
confidence: 99%
“…60 for a review till year 2005). More recently the RNGH instability has gained popularity as it has been invoked in order to understand the hot topics of spontaneous frequency-comb formation and self modelocking in quantum-dot and quantum-cascade lasers 19,20,24,61,62 .…”
mentioning
confidence: 99%